ANALYSIS OF WEAKNESSES IN EVALUATION METHODOLOGY OF SOVEREIGN CREDIT RATING AGENCIES. (Лучшие интеллектуальные исследования, 2025)
The purpose of this article is "One of the goals set by our President Sh.M. Mirziyoyev in the 2030 strategy of the new Uzbekistan" is the issues that are an obstacle to the transfer of the sovereign credit rating from BB to BBB and the neighboring the path of the countries in this regard and the evaluation criteria of the rating agencies, which are at the top of the world rating agencies, are discussed.